The ANeED study – ambroxol in new and early dementia with Lewy bodies (DLB): protocol for a phase IIa multicentre, randomised, double-blinded and placebo-controlled trial - Chwiszczuk, Luiza Jadwiga; Breitve, Monica Haraldseid; Kirsebom, Bjørn-Eivind Bordewick; Selnes, Per; Fløvig, John Chr.; Knapskog, Anne-Brita; Skogseth, Ragnhild E.; Hubbers, Jessica; Holst-Larsen, Elin; Rongve, Arvid (Frontiers in Aging Neuroscience, 2023)
Background Currently, there are no disease-modifying pharmacological treatment options for dementia with Lewy bodies (DLB). The hallmark of DLB is pathological alpha-synuclein (aS) deposition. There are growing amounts of data suggesting that reduced aS clearance is caused by failure in endolysosomal and authophagic pathways, as well as and glucocerebrosidase (GCase) dysfunction and mutations in the GCase gene (GBA). The population’s studies demonstrated that the incidence of GBA mutations is higher among Parkinson’s disease (PD) patients, and carriers of such mutations have a higher risk of developing PD. The incidence of GBA mutations is even higher in DLB and a genome-wide association study (GWAS) confirmed the correlation between GBA mutations and DLB. In vivo experiments have shown that ambroxol (ABX) may increase GCase activity and GCase levels and therefore enhance aS autophagy-lysosome degradation pathways. Moreover, there is an emerging hypothesis that ABX may have an effect as a DLB modifying drug. The aims of the study “Ambroxol in new and early Dementia with Lewy Bodies (ANeED) are to investigate the tolerability, safety and effects of ABX in patients with DLB. Methods This is a multicentre, phase IIa, double-blinded, randomised and placebo-controlled clinical trial, using a parallel arm design for 18 months’ follow-up. The allocation ratio is 1:1 (treatment:placebo). Discussion The ANeED study is an ongoing clinical drug trial with ABX. The unique, but not fully understood mechanism of ABX on the enhancement of lysosomal aS clearance may be promising as a possible modifying treatment in DLB. Trial Registration The clinical trial is registered in the international trials register – clinicaltrials.com (NCT0458825) and nationally at the Current Research Information System in Norway (CRISTIN 2235504).